AMBIGUITAS KODE ETIK ADVOKAT DALAM MASALAH PENGGUNAAN IKLAN DAN PUBLISITAS - Rizal Sirojudin, Muhammad (Lex Librum : Jurnal Ilmu Hukum, 2026)
Each profession has its own code of ethics, including advocates. Of course, the Code of Ethics should be clear so that the act creates ambiguity in its application like a law. However, when viewed from the Indonesian Advocates' Code of Ethics there is a gray area, namely the prohibition of advertising and publicity of advocates as stated in articles 8 (B) and 8 (F). This is a problem because the advocate profession is basically a service profession as in general which of course requires advertising in terms of marketing. In this study, the author uses a normative approach and a law in action approach. This study concludes that there is an unclear prohibition on advertising and publication in the Advocate's Code of Ethics and this prohibition can be political in its implementation. This research is expected to be a trigger for discussion on the revision of the Indonesian Advocates' Code of Ethics and hopes that this will be a guide to the application of the advocate's code of ethics in the issue of prohibition of advertising and publicity carried out by advocates.